Characteristics of value based organic food chains: two cases from Slovenia - Prišenk, Jernej; Borec, Andreja (Applied Studies in Agribusiness and Commerce, 2016)
In the literature the value based food chains express two main characteristics: business relationships among strategic partners interacting in the supply chain are based on a written set of values and food products are differentiated from similar food products (Stevenson, 2009). To verify the first part of the definition the analysis of two organic food chains were carried out. For the analysis of business relationships and food quality communication in the food chain two different methodological approaches were used. For collecting the input data semi-structured interviews of various stakeholders were performed. The results of the analyzed case studies show the characteristics of value based food chains could be broader and more complex if some additional perspectives were considered.